Dermatoscopic features of cutaneous non-facial and non-acral lentiginous growth pattern melanomas - Jeff Keir (Mattioli1885, 2014)
Background: The dermatoscopic features of facial lentigo maligna (LM), facial lentigo maligna melanoma (LMM) and acral lentiginous melanoma (ALM) have been well described. This is the first description of the dermatoscopic appearance of a clinical series of cutaneous non-facial non-acral lentiginous growth pattern melanomas. Objective: To describe the dermatoscopic features of a series of cutaneous non-facial non-acral lentiginous growth pattern melanomas in an Australian skin cancer practice. Method: Single observer retrospective analysis of dermatoscopic images of a one-year series of cutaneous non-facial, non-acral melanomas reported as having a lentiginous growth pattern detected in an open access primary care skin cancer clinic in Australia. Lesions were scored for presence of classical criteria for facial LM; modified pattern analysis ("Chaos and Clues") criteria; and the presence of two novel criteria: a lentigo-like pigment pattern lacking a lentigo-like border, and large polygons. Results: 20 melanomas occurring in 14 female and 6 male patients were included. Average patient age was 64 years (range: 44-83). Lesion distribution was: trunk 35%; upper limb 40%; and lower limb 25%. The incidences of criteria identified were: asymmetry of color or pattern (100%); lentigo-like pigment pattern lacking a lentigo-like border  (90%); asymmetrically pigmented follicular openings (APFO's) (70%); grey blue structures (70%);  large polygons (45%); eccentric structureless area (15%); bright white lines (5%). 20% of the lesions had only the novel criteria and/or APFO's. Limitations: Single observer, single center retrospective study. Conclusions: Cutaneous non-facial non-acral melanomas with a lentiginous growth pattern may have none or very few traditional criteria for the diagnosis of melanoma. Criteria that are logically expected in lesions with a lentiginous growth pattern (lentigo-like pigment pattern lacking a lentigo-like border, APFO's) and the novel criterion of large polygons may be useful in increasing sensitivity and specificity of diagnosis of these lesions. Further study is required to establish the significance of these observations.